What went wrong? Explaining strategic foundations of the crisis in Ukraine - A. A. Sushentsov (Ибероамериканские тетради)
Moscow does not deny the significance of the security interests of small states, but it is important to recognize the security interests of all actors in the system, including the larger ones. The history of the Cold War clearly shows that a stable system of confrontation management and conflict resolution is possible. Russia’s proposals for an inclusive security system in Europe have been ignored multiple times. One reason explaining the reluctance to take Russian proposals into consideration is that, geopolitically, time is structured differently for Russia and for the West. The understanding of the West is linked to national electoral cycles. Whereas for Russia, geopolitical time is measured by epochs that are outlined starting with major historical events: wars, peace treaties and political cataclysms. The conflict in Ukraine turned out to be a point where these contradictions came to concentrate.